MANIFESTATION OF MAXIMAL ISOMETRIC MUSCLE STRENGTH AMONG SELECTED FEMALE HANDBALL PLAYERS OF DIFFERENT AGES - Živojin Maksić; Marko Isaković; Goran Vučković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
A sample of 57 subjects consisting of selected junior female players, aged 13 or 14, was used to measure maximal isometric muscle strength for certain muscle groups, more specifically, for hand flexors (dominant and non-dominant), back extensors and leg extensors. The main morphological parameters of the 14-year old subjects were the following: BH±SD = 1.719±0.065 meter; BM±SD = 64.36±6.36 kilogram; BMI±SD = 21.78±1.93 (kg/m2), and for the 13-year olds they were: BH±SD = 1.667±0.056 meter; BM±SD = 58.71±9.87 kilogram; BMI±SD = 21.01±2.58 (kg/m2). Based on the obtained descriptive statistics results, a conclusion can be drawn that the mean value for the variable of the dominant hand grip amounted to 33.87±4.92 daN with the 14-year old subjects and 28.58±5.98 daN with the 13-year old ones, whereas the mean values for the non-dominant hand grip were 30.94±4.24 daN and 25.36±5.50 daN, respectively. The values for the variable of back extensors force showed mean values of 87.28±13.41 daN; 77.22±12.19 daN, respectively, whereas the mean values for leg extensors were 86.19±12.65 daN; 76.01±18.19 daN, respectively. Based on the results of Students' test, it can be concluded that the results obtained for the variables that measured the maximum isometric force of the flexors of the dominant hand, nondominant hand, back extensors, and leg extensors, there is a statistically significant difference at 95% probability level, because t = 13.095, p = 0.001; t = 18.065, p = 0.000; t = 8.798, p = 0.004; t = 5.891, p = 0.019, respectively.